PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL PADA SISWA SMK JURUSAN TEKNIK KENDARAAN RINGAN: KAJIAN LITERATUR - Febri Muhamad Taufik (Jurnal Binagogik, 2025)
The development of technology has transformed various aspects of life, including education. At the Vocational High School (SMK) level, particularly in the Automotive Engineering department, digital learning media plays a crucial role in enhancing the quality of education. This research is a literature review of 25 articles published between 2021 and 2025, aiming to identify the forms of digital media that align with the characteristics of the subject matter and the challenges of implementation in the field. The analysis results indicate that the form and complexity of the media are heavily influenced by the difficulty level of the material. More complex media such as Virtual Reality and Augmented Reality are used for practical materials, while e-modules and tutorial videos are more suitable for theoretical content. The main implementation challenges include infrastructure availability, teacher competency, and student backgrounds. This study recommends the importance of developing contextual, affordable, and easily accessible learning media for all students. The research is limited to publications from the last five years and does not analyze the long-term impact of learning media on students' work competencies.